Targeting the overexpressed USP7 inhibits esophageal squamous cell carcinoma cell growth by inducing NOXA‐mediated apoptosis. Issue 1 (21st September 2018) - Hu, Tao; Zhang, Jingyang; Sha, Beibei; Li, Miaomiao; Wang, Longhao; Zhang, Yi; Liu, Xingge; Dong, Ziming; Liu, Zhenzhen; Li, Pei; Chen, Ping
Abstract : Increasing evidence suggests that deubiquitinase USP7 participates in tumor progression by various mechanisms and serves as a potential therapeutic target. However, its expression and role in esophageal cancer remains elusive; the anti‐cancer effect by targeting USP7 still needs to be investigated. Here, we reported that USP7 was overexpressed in esophageal squamous cell carcinoma (ESCC) tissues compared with adjacent tissues, implying that USP7 was an attractive anticancer target of ESCC. Pharmaceutical or genetic inactivation of USP7 inhibited esophageal cancer cells growth in vitro and in vivo and induced apoptosis. Mechanistically, inhibition of USP7 accumulated poly‐ubiquitinated proteins, activated endoplasmic reticulum stress, and increased expression of ATF4, which transcriptionally upregulated expression of NOXA and induced NOXA‐mediated apoptosis. These results provide an evidence for clinical investigation of USP7 inhibitors for the treatment of ESCC.